Analisis Kepuasan Pengguna BPJS Kesehatan dan Perbandingannya dengan Asuransi Swasta di Kabupaten Kuningan - Isnaeni Ayuningtias; Iyan Pebriyana; Maedina; Muhammad Choerul Ridwan; Nabila Safitri (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
The purpose of this study is to determine how much public satisfaction with public services related to BPJS Health, case study (BPJS Health Users in Kuningan Regency) It will conduct an analysis from internal and external aspects, with internal analysis including factors such as the level of new customer acquisition, customer acquisition, response to customer complaints, customer satisfaction, and customer benefits. This research uses a mixed method with quantitative and qualitative data collection techniques with a descriptive design. The results showed that there were several levels of customer satisfaction that were still below expectations, such as services in the attitude of doctors and nurses to patients. Customers still experience shortcomings in BPJS Health services, especially in terms of services provided. Keywords: Public Satisfaction, Public Services, BPJS Health